The LJ System-Development and Validation of a Reliable and Simple Device for Bronchoscopic Measurement of Distances Within the Tracheobronchial Tree - Sestakova, Zuzana; Nemcova, Sarka; Denk, Petr; Pechkova, Veronika; Michalek, Pavel; Votruba, Jiri (Diagnostics (Basel, Switzerland), 2025)
Background: The accurate measurement of the distances within the airways during bronchoscopy is necessary for diagnostic purposes; however, a reliable and simple device does not exist. Methods: The LJ system, consisting of a probe, a box with a display, an encoder, and a microcontroller, has been developed, and its prototype has been tested in vitro and validated in clinical practice in suitable procedures of interventional bronchoscopy. Results: In vitro, the device measurements showed a good correlation with the control performed with a digital caliper. Subsequently, ten patients were included in a pilot study evaluating this novel prototype of a measurement device. The device was used on four patients with tracheal stenosis indicated for Y-stent placement, four patients indicated for open surgery, and two cases of tracheoesophageal fistula. The measurements have been validated using computed tomography imaging or by direct inspection and measurement during open surgical procedures. Conclusions: The first experience and pilot study evaluating this novel instrument for distance measurements during interventional bronchology procedures showed that the LJ device can provide precise readings of the distance from the vocal cords, the lengths of tracheal stenoses, or the size of tumorous and other lesions. Its use might be widened to other endoscopic indications.
Keywords: measurement device; stent placement; interventional bronchology; airway distance measurement